2011
DOI: 10.1007/s10646-011-0665-6
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline adsorption on kaolinite: pH, metal cations and humic acid effects

Abstract: Contamination of environmental matrixes by human and animal wastes containing antibiotics is a growing health concern. Because tetracycline is one of the most widely-used antibiotics in the world, it is important to understand the factors that influence its mobility in soils. This study investigated the effects of pH, background electrolyte cations (Li(+), Na(+), K(+), Ca(2+) and Mg(2+)), heavy metal Cu(2+) and humic acid (HA) on tetracycline adsorption onto kaolinite. Results showed that tetracycline was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(66 citation statements)
references
References 31 publications
7
58
0
1
Order By: Relevance
“…The preparation of sorbents was conducted according to the previous study (Zhao et al 2011). The specific surface area of kaolinite and montmorillonite was 22.3 and 46.0 m 2 g −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of sorbents was conducted according to the previous study (Zhao et al 2011). The specific surface area of kaolinite and montmorillonite was 22.3 and 46.0 m 2 g −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Generally, tetracyclines, behave positive (pH <3.3), neutral (3.3 <pH <7.68) or negative (pH > 7.68) (Zhao et al, 2011b). The tetracyclines are strong chelating agents and pH dependent, and they have their antibacterial activity and pharmacokinetics decreased when associated with foods rich in calcium, iron, magnesium and other minerals or antacids such as sodium bicarbonate, which increase the pH in the stomach.…”
Section: Properties Of the Tetracyclinesmentioning
confidence: 99%
“…Residues of antibiotics, including tetracyclines from Wastewater Treatment Plants (WWTPs) of urban and agricultural effluents are frequently detected in surface water, groundwater, soils and sediments (Zhao et al, 2011b).…”
Section: Occurrence In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Few authors have reported the effect of iron on the extent of adsorption of antibiotics onto clay minerals (Campbell and Hasinoff 1991;Zhao et al 2011). To study this effect for Iraqi montmorillonite, the concentration of the available iron in the montmorillonite was determined with ICP-MS and found to be 252 lg g 21 (0.0045 mmol Fe g -1 ).…”
Section: Effect Of Iron Content On Adsorptionmentioning
confidence: 99%